Case Report: Diagnosis and Management of Pin-Headscarf at The Bronchial Segment In RSUP Dr. M Djamil Padang - Wahyu Julianda; Ade Asyari (Journal of Agromedicine and Medical Sciences, 2021)
Introduction: Foreign body aspiration into the airway is a common case in children. Scarf pin aspiration often occurs in women who wear the hijab. A bronchoscopy is an option in the management of foreign body aspiration cases. However, other treatments such as thoracotomy can be considered, if the management of foreign body aspiration fails using rigid bronchoscopy. Case Report: Reported one case of a 12-year-old girl who complained of inhaling scarf pin 1 day before being admitted to hospital. Chest X-ray found radiopaque foreign body projection as high as spatium intercostal V with right lower lobe projection. The patient was diagnosed with foreign body pin scarf et right bronchus and was treated with a rigid bronchoscopy but it was not successfully extracted, one and a half months later the patient was performed Video-assisted thoracic surgery but failed to re-extract, then the foreign bodies were successfully extracted after the thoracotomy. Conclusion: Migration of pins into the bronchial segments as high as spatium intercostal V projections right lower lobe and left lower lobe will be difficult to locate and extract with rigid bronchoscopy. Thoracotomy is further management for scarf pin aspiration that fails to be treated by rigid bronchoscopy. Keywords: foreign body, scarf pin, bronchoscopy, segment bronchi, thoracotomy